Analisis Harga Pokok Penjualan terhadap Perubahan Laba Kotor di Masa Covid-19 pada Apotek Pelangi Farma Subang Tahun 2018-2020 - Agus Sumitra; Fajar Adhi Purwaningrum; Adine Setya Wardhani (Pusat Riset dan Inovasi Nasional, 2022)
This research was conducted at Apotek Pelangi Farma Subang, because during the Covid-19 period pharmacies became a very vital business field and were the spearhead between the interests of pharmaceutical supply and the interests of the community to obtain medicines or all kinds of needs to support health. The purpose of this study is to determine the determination of Cost of Goods Sold (COGS) and how much gross profit is obtained, and whether the profit is optimal. This research uses Descriptive Analysis method by calculating quantitative data and analyzing financial statements and expressed with qualitative data to interpret the results of data calculations. The results of this study indicate that gross profit is a change in deduction from sales minus cost of goods sold. While the cost of goods sold is a calculation of the initial inventory plus purchases minus the final inventory, so that the cost of goods sold from 2018 to 2020 has increased and the profit obtained is optimal.